Oxidative Stress and Its Significant Roles in Neurodegenerative Diseases and Cancer - Thanan, Raynoo (Int J Mol Sci, 2014)
Reactive oxygen and nitrogen species have been implicated in diverse pathophysiological conditions, including inflammation, neurodegenerative diseases and cancer. Accumulating evidence indicates that oxidative damage to biomolecules including lipids, proteins and DNA, contributes to these diseases. Previous studies suggest roles of lipid peroxidation and oxysterols in the development of neurodegenerative diseases and inflammation-related cancer. Our recent studies identifying and characterizing carbonylated proteins reveal oxidative damage to heat shock proteins in neurodegenerative disease models and inflammation-related cancer, suggesting dysfunction in their antioxidative properties. In neurodegenerative diseases, DNA damage may not only play a role in the induction of apoptosis, but also may inhibit cellular division via telomere shortening. Immunohistochemical analyses showed co-localization of oxidative/nitrative DNA lesions and stemness markers in the cells of inflammation-related cancers. Here, we review oxidative stress and its significant roles in neurodegenerative diseases and cancer.